2021
DOI: 10.1002/dys.1677
|View full text |Cite
|
Sign up to set email alerts
|

Developmental dyslexia and creativity: A meta‐analysis

Abstract: Despite difficulties in reading and writing, some research suggests that dyslexia may be related to higher levels of creativity. However, this pattern is not consistently observed. The current research sought to ascertain whether individuals with clinically diagnosed dyslexia exhibit higher creativity than controls through a meta‐analysis. Fourteen studies that assessed the creativity of 397 individuals with clinically diagnosed dyslexia and 453 controls were reviewed. Random‐effects meta‐analysis revealed an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 80 publications
3
15
1
1
Order By: Relevance
“…Such findings align with the results of another study which showed that students with DD performed significantly better on tasks that involved connecting unusual combinations of ideas supporting new possibilities and original solutions (Cancer et al, 2016). Two recent meta-analyses highlight that a consistent creative advantage is not always found in children and adolescents with dyslexia (Erbeli et al, 2021a;Majeed et al, 2021). However, Erbeli et al (2021a) found that compared with adolescents, adults with dyslexia did show a creative advantage over non-dyslexic adults.…”
Section: Divergent Thinkingsupporting
confidence: 84%
See 2 more Smart Citations
“…Such findings align with the results of another study which showed that students with DD performed significantly better on tasks that involved connecting unusual combinations of ideas supporting new possibilities and original solutions (Cancer et al, 2016). Two recent meta-analyses highlight that a consistent creative advantage is not always found in children and adolescents with dyslexia (Erbeli et al, 2021a;Majeed et al, 2021). However, Erbeli et al (2021a) found that compared with adolescents, adults with dyslexia did show a creative advantage over non-dyslexic adults.…”
Section: Divergent Thinkingsupporting
confidence: 84%
“…Initial evidence also suggests that enhanced creativity in individuals with dyslexia may be more pronounced in females than males (Erbeli et al, 2021a). Majeed et al (2021) also found that in the adult samples, individuals with dyslexia significantly out-performed those without dyslexia on creativity scores.…”
Section: Divergent Thinkingmentioning
confidence: 88%
See 1 more Smart Citation
“…Furthermore, differences in moral reasoning may help neurodivergent researchers to identify ethical or epistemological issues which would otherwise remain uncovered. This difference in moral reasoning reflects a larger heterogeneity of information processing across the neurodiversity spectrum, including differences in creative or divergent thinking (Best et al, 2015;Colautti et al, 2021;Magenes et al, 2021;Majeed et al, 2021;Sedgwick et al, 2019), vocabulary and reading experience (e.g., Elsherif et al, 2021), pattern recognition (Baron-Cohen et al, 2009;Schneps et al, 2011), and the influence of cognitive biases (Rozenkrantz et al, 2021). In particular, cognitive biases such as confirmation bias have been identified as a key issue in the interpretation of scientific results.…”
Section: Part 2: Synergistic Relationship Between Neurodiversity and ...mentioning
confidence: 99%
“…Others, however, using a variety of definitions and measures of creativity, report no differences (Alves & Nakano, 2014; Łockiewicz, Bogdanowicz, & Bogdanowicz, 2014; Mourgues, Preiss, & Grigorenko, 2014; Ritchie, Luciano, Hansell, Wright, & Bates, 2013). Two recent meta‐analyses of dyslexia and creativity have helped to resolve some of this inconsistency: both found that while readers with dyslexia as a group are no more creative than those without dyslexia, adults with dyslexia (but not children or adolescents) are significantly more creative than adults without dyslexia (Erbeli, Peng, & Rice, 2022; Majeed, Hartanto, & Tan, 2021). Of course, it may not be the measured ability itself that is important: readers with dyslexia are widely believed to be creative (anecdotal evidence abounds of dyslexic designers, architects and artists – see Brunswick, 2009), so it may be that perception of one's own creativity will be evident amongst these readers irrespective of their actual ability.…”
Section: Introductionmentioning
confidence: 99%